2009
DOI: 10.1007/s12328-009-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced gastric cancer associated with nodular gastritis in a young patient

Abstract: A 20-year-old female underwent an endoscopy for epigastralgia that revealed many small, elevated nodules in the antrum that were diagnosed as nodular gastritis. The endoscopy also showed an ulcerative lesion with an uneven round wall at the greater curvature of the middle corpus. Biopsy of the ulcerative lesion yielded a diagnosis of poorly differentiated adenocarcinoma. A distal gastrectomy was performed on the basis of a diagnosis of gastric cancer associated with nodular gastritis. The intraoperative findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…NG may also contribute to the development of diffuse-type gastric carcinoma of the gastric body [4]. Although the mean age of gastric cancer associated with NG is reportedly 34 years, cases in the teens or twenties have also been observed, with 97-100% of patients exhibiting diffuse-type gastric carcinoma [5,11]. NG may be associated with severe pangastritis, which has been strongly linked to a risk of gastric cancer, particularly diffuse-type, in both clinical and basic studies [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NG may also contribute to the development of diffuse-type gastric carcinoma of the gastric body [4]. Although the mean age of gastric cancer associated with NG is reportedly 34 years, cases in the teens or twenties have also been observed, with 97-100% of patients exhibiting diffuse-type gastric carcinoma [5,11]. NG may be associated with severe pangastritis, which has been strongly linked to a risk of gastric cancer, particularly diffuse-type, in both clinical and basic studies [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Currently recognized as a type of Helicobacter pylori (H. pylori)-associated gastritis, NG is also considered a high risk factor for diffuse-type gastric carcinoma of the gastric body [4]. Although gastric cancer associated with NG in the teens or twenties has been described [5,6], reports are scarce on young patients with gastric cancer developing after eradication, and its clinical course remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Age was one of the most critical risk factors for GC ( 15 , 16 ). Here, we assessed the risk of developing SPM after GC in different age subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NG is 0.05–3.1% in adult patients undergoing EGD, with >90% of those patients testing positive for H. pylori . It has been suggested that NG in young adult patients with H. pylori infection might be the risk factor for development of diffuse type gastric carcinoma …”
mentioning
confidence: 99%
“…[13][14][15][16][17] It has been suggested that NG in young adult patients with H. pylori infection might be the risk factor for development of diffuse type gastric carcinoma. [18][19][20][21][22][23] Although the detection of NG on EGD is typical in H. pylori-infected children, the key elements of the mucosal immune response leading to lymphoid hyperplasia are not clear. Whereas our previous study showed altered expression of genes related to the immune response in the gastric mucosa of children with H. pylori infection compared with children without H. pylori infection, 24 a comparison between children and adults would be more likely to elucidate the mechanisms of development of NG.…”
mentioning
confidence: 99%